Assessment of paleo-recharge under the Fennoscandian Ice Sheet and its impact on regional groundwater flow in the northern Baltic Artesian Basin using a numerical model - Vaikmäe, Rein; Sterckx, Arnaud; Lemieux, Jean-Michel (Hydrogeology Journal, 2020)
The study investigates the mechanism of glacial meltwater recharge under the Fennosciandian Ice Sheet during the last glacial maximum (LGM) and its impact on regional groundwater flow in the northern Baltic Artesian Basin (BAB) in Estonia and Latvia. The current hypothesis is that a flow reversal occurred in the BAB due to subglacial recharge during the LGM. This hypothesis is supported by an extensive dataset of geochemical and isotopic measurements in the groundwater of northern Estonia, exhibiting significant depletion in δ18O with respect to modern precipitation. To verify the consistency of this hypothesis and better understand groundwater flow dynamics during the LGM period, a numerical model is developed for this area. Two cross-sectional models have been created across the northern BAB, in which groundwater flow and the transport of δ18O have been simulated from the beginning of the LGM to present-day. Several simulations were performed with different subglacial boundary conditions, to investigate the uncertainty related to subglacial recharge of meltwater during the LGM and the subsequent flow reversal in the northern BAB. Several simulations provide a satisfying fit between computed and observed values of δ18O, which means that the hypothesis of subglacial recharge of meltwater is consistent with δ18O distribution. The numerical model suggests that preservation of meltwater in northern Estonia is controlled by confining layers and the proximity to the outcrop area of aquifers, located in the Gulf of Finland. The results also suggest that glacial meltwater has been preserved under the Baltic Sea in the Gulf of Riga.